Synthesis of porous amorphous FePO4 nanotubes and their lithium storage properties - Lim, Tuti Mariana (2013)
Holey pipes: An oil-phase chemical route was used to prepare porous amorphous a-FePO4 nanotubes. In the etching process, Fe2O3 reacted with weak acid, resulting in nanotubes with a pore size of 2–10 nm. The porous nanotubes show good cathode performance in lithium ion batteries owing to their hollow structure and small pore size.